Salt Bridges Regulate in Silico Dimers Formation for β2-Microglobulin Amyloidogenic Variants - Maschio, Maria Celeste; Brancolini, Giorgia; Corni, Stefano (Journal of Self Assembly and Molecular Electronics, 2023)
β2-microglobulin is a paradigmatic amyloidogenic protein responsible for dialysis-related amyloidosis, a disease associated to long-term hemodialyzed patients and characterized by accumulation of amyloid deposits in the osteoar- ticular tissues. In the early stages of amyloid fibril formation, β2-microglobulin associates into dimers and higher oligomers, but clarifications are still needed for the triggering conditions, mechanisms and specificity of dimer forma- tion. To characterize the dimeric association process, the protein-protein interactions between three different species are investigated: namely, the native protein and the two amyloidogenic variants ΔN6 and D76N. The dimerization process is rationalized relying on state of the art computational methods. A comparative mechanism for how different mutations in the three variants can affect protein dimerization and thus fibril formation is proposed. The number of salt bridges involved at the protein-protein interface correlates with the degree of amyloidogenicity of each individual species. The findings can offer possible strategies in controlling the dimerization mechanism based on different β2-microglobulin protein mutations, which have significant roles in the fibrillogenical process.